In vitro evaluation of endothelial exosomes as carriers for small interfering ribonucleic acid delivery - Banizs AB (Dove Medical Press, 2014)
Anna B Banizs,1 Tao Huang,1 Kelly Dryden,2 Stuart S Berr,1 James R Stone,1 Robert K Nakamoto,2 Weibin Shi,1 Jiang He1 1Department of Radiology and Medical Imaging, 2Department of Molecular Physiology and Biological Physics, University of Virginia, Charlottesville, VA, USA Abstract: Exosomes, one subpopulation of nanosize extracellular vesicles derived from multivesicular bodies, ranging from 30 to 150 nm in size, emerged as promising carriers for small interfering ribonucleic acid (siRNA) delivery, as they are capable of transmitting molecular messages between cells through carried small noncoding RNAs, messenger RNAs, deoxyribonucleic acids, and proteins. Endothelial cells are involved in a number of important biological processes, and are a major source of circulating exosomes. In this study, we prepared exosomes from endothelial cells and evaluated their capacity to deliver siRNA into primary endothelial cells. Exosomes were isolated and purified by sequential centrifugation and ultracentrifugation from cultured mouse aortic endothelial cells. Similar to exosome particles from other cell sources, endothelial exosomes are nanometer-size vesicles, examined by both the NanoSight instrument and transmission electron microscopy. Enzyme-linked immunosorbent assay analysis confirmed the expression of two exosome markers: CD9 and CD63. Flow cytometry and fluorescence microscopy studies demonstrated that endothelial exosomes were heterogeneously distributed within cells. In a gene-silencing study with luciferase-expressing endothelial cells, exosomes loaded with siRNA inhibited luciferase expression by more than 40%. In contrast, siRNA alone and control siRNA only suppressed luciferase expression by less than 15%. In conclusion, we demonstrated that endothelial exosomes have the capability to accommodate and deliver short foreign nucleic acids into endothelial cells. Keywords: extracellular vesicles, exosomes, gene delivery, siRNA, endothelium